Quality Between Government and Non-Governmental Organizations (NGOs) in Waste Management Efforts: Quality Antara Pemerintah dan Lembaga Swadaya Masyarakat (Lsm) dalam Upaya Pengelolaan Sampah - Jayanti, Mery Tri; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2020)
The Gresik Environmental Service's partnership with NGOs ECOTON and ASBAG which focuses on waste management in environmental management. This study aims to determine the partnership between the Government, NGOs, PKK, the community in waste management and the obstacles. This study used a qualitative descriptive research method. The technique of determining the informants used purposive sampling and data collection techniques, namely through the methods of observation, interviews and document analysis. This research focuses on equity, transparency, mutual benefit. The data analysis technique uses the Miles and Huberman model in Sugiyono (2014: 246), namely data collection, data reduction, data presentation, drawing conclusions.